ANALISIS KELAYAKAN USAHATANI PADI SAWAH (Oryza sativa) TADAH HUJAN (STUDI KASUS DI DESA SUNGAI DUA KECAMATAN RAMBUTAN KABUPATEN BANYUASIN) - Yuwinti Nearti; Budi Fachrudin; Rahmah Awaliah (Agribusiness Study Program Universitas Sriwijaya in Collaboration with Indonesian Society of Agricultural Economics (PERHEPI/ISAE), 2020)
Food security can be established in agricultural sector as a main supplier of foods (Sumastuti, 2010). Agricultural sector especially subsector of crops plays an important rule for the life of Indonesian people as the source of foods and nutritions. It relates to the fact that rice comodity is not only as a main supply of foods but also has a strategic rule, causes the dynamical price and the inflation of macro variable in the national economics (BPS, 2015). This research aims to describe farmers income by evalutating the production costs and the ability to run the business according to R/C ratio. The research used survey method and purposive sampling. The population of this research were 43 farmers having rainfed land affected by tidal. The number of sampling used Slovin formulation with 10% error standard, as 30 farmers in Sungai Dua Village Sub-District Rambutan Banyuasin Regency were involved as respondents. The analysis method used income and feasibility study. The results showed thatthe average production was 6.522 Kg as the average revenue was 29.349.505/Ha/MT. Total cost was Rp. 14.337.467/Ha/MT as the income was Rp. 15.012.038/Ha/MT. Rice faming in Sungai Dua Village Sub-District Rambutan Banyuasin Regency was feasible with the 2.05 RCR value. It means that for each Rp. 1.000 cost rice famers would gain Rp.2.050. revenue.